Terminal Deoxynucleotidyl Transferase (TdT) Positive Acute Myeloid Leukemia with C-MYC and BCL2 Expression: A Distinct Biological Entity with Potential Clinical Implications - Panigrahi, Chinmayee; Bhuyan, Biswajit; Das, Prabodha Kumar; Padhi, Somanath; Chhabra, Gaurav; Panigrahi, Ashutosh; Choudhary, Arushi; Sudarsini, Saheeta; Acharya, Prapti; Jash, Debasis (Indian Journal of Medical and Paediatric Oncology, 2025)
Terminal deoxynucleotidyl transferase (TdT) is a unique deoxyribonucleic acid polymerase whose overexpression has been used as an important biomarker in the diagnosis of precursor B or T cell acute lymphoblastic leukemia/lymphoma. Over the last few years, TdT has been increasingly implicated in the genesis of mutant Fms-like tyrosine kinase 3-internal tandem duplication (FLT3-ITD) and NPM1 isoforms, two key events in the myeloid stem cell leukemogenesis. This article studies the diagnostic and prognostic implications of immunoexpression of TdT, C-MYC, and BCL2 in acute myeloid leukemia (AML). We retrospectively reviewed seven cases of TdT positive (+), myeloperoxidase negative AMLs (2022–2024) with C-MYC and/or BCL2 expression by immunohistochemistry (IHC), and correlated these with flow cytometric (FC), molecular, and/or cytogenetics data (wherever available) along with outcome following induction chemotherapy. Morphologically, all these cases resembled French-American-British M0, M1, and M5 AMLs, or even high-grade lymphoproliferative neoplasms with moderate to stronger nuclear positivity for TdT and C-MYC in a higher proportion neoplastic cell along with stronger cytoplasmic BCL2 expression. Two were FLT3-ITD mutated, one was TP53 mutated, one had high-risk cytogenetics, whereas the remainder had no detectable abnormalities on molecular testing with variable degree of therapeutic response. Literature review highlighted the negative impact of overall, event-free, and relapse-free survivals among TdT and C-MYC positive AMLs whereas BCL2 expressors were likely to have increased chemoresistance. We suggest that TdT +/C-MYC +/BCL2+ AMLs may serve as distinct biological subtype; and IHC/FC-based testing should be a part of routine diagnostic workup for better risk stratification in AMLs.
Keywords: immunohistochemistry; TdT; myeloid leukemia; molecular testing; prognosis